Desenvolvimento de microcélula eletroquímica para estudos de microrregiões - Akita, Adriano Heleno [UNESP]; Barragan, José Tiago Claudino [UNESP]; Fugivara, Cecílio Sadao [UNESP]; Benedetti, Assis Vicente [UNESP] (Sociedade Brasileira de Química, 2012)
The construction and optimization of a device that can be applied to electrochemical studies in flat micro regions are described. This was developed as an attempt to study small regions of metallic samples, whose properties may differ completely from its macroscopic behavior and for studies in highly resistive medium. Some results were obtained for individual grains of polycrystalline samples, welded regions, pure copper, platinum, glassy carbon, single crystals of Cu-Zn-Al alloy, and steel in biodiesel without electrolyte intentionally added. The device showed to be useful for the proposed purpose, allowing to be automated and has potential possibilities of other applications.
Development of an electrochemical microcell for studies of micro regions
Keywords: electrochemical microcell; scanning droplet cell; localized electrochemical analysis